Composite materials based on ferroelectric nematic liquid crystals and devices containing same - Patents.com
Patent Information
- Application Number
- JP2024541655
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-10
- Filing Date
- 2023-01-10
- Publication Date
- 2025-02-19
Smart Images

Figure 2025504799000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 63 / 298,116, filed January 10, 2022, and entitled SUPERPARAELECTRIC COMPOSITE MATERIAL BASED ON FERROELECTRIC NEMATIC LIQUID CRYSTALS, the contents of which are incorporated herein by reference to the extent not conflicting with this disclosure.
[0002] Federally Funded Research This invention was made with Government support under Grant No. DMR1710711 awarded by the National Science Foundation. The Government has certain rights in this invention.
[0003] The present disclosure relates generally to composite materials that include ferroelectric nematic liquid crystals. More specifically, embodiments of the present disclosure relate to composite materials that include one or more porous materials and ferroelectric nematic liquid crystals within the pores of the one or more porous materials. [Background technology]
[0004] Ferroelectricity in liquids was predicted in the 1910s by P. Debye and M. Born, who applied the Langevin-Weiss model of ferromagnetism to the orientational order of molecular electric dipoles. Recently, there has been growing interest in nematic ferroelectricity, which offers new opportunities for liquid crystal science and technology due to its unique combination of macroscopic polar order and fluidity.
[0005] Any discussion of problems and solutions set forth in this section is included in this disclosure solely for the purpose of providing a context for the present disclosure, and should not be construed as an admission that any or all of the discussion was publicly known at the time the invention was made. Summary of the Invention [Problem to be solved by the invention]
[0006] This Summary is provided to introduce selected concepts. It is not necessarily intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter.
[0007] Embodiments of the present disclosure relate to composite materials comprising ferroelectric nematic liquid crystals. As described in more detail below, the composite materials can be used to form a variety of devices having desired properties, such as a high dielectric constant and / or desired electro-optical properties. [Means for solving the problem]
[0008] According to embodiments of the present disclosure, the composite material includes a first porous material having pores, the pores having a volume, and a ferroelectric nematic liquid crystal, the volume of the pores of the first porous material containing the ferroelectric nematic liquid crystal. The pores can be filled or substantially filled with the ferroelectric nematic liquid crystal. According to various embodiments of the present disclosure, the first porous material can be a solid. According to additional embodiments, the first porous material can be, for example, a polymer, a glassy, a crystalline, an amorphous, a foam, an aerogel, or a porous ceramic. The composite material can include an additional porous material and / or a ferroelectric nematic liquid crystal. The second porous material can be the same as or different from the first porous material.
[0009] According to additional embodiments of the present disclosure, the composite material (e.g., dielectric medium) includes a ferroelectric nematic liquid crystal and a solid material, the solid material being dispersed in the liquid crystal as fine particles. The solid material can be or include, for example, ferroelectric or superparaelectric particles. The dispersion can be formed, for example, by phase separation or photopolymerization. According to further embodiments, the dispersion is stabilized by amphiphilic molecular components.
[0010] The composite materials and / or dielectric media described herein can be used to form, for example, semiconductor structures or devices, dielectric structures, capacitors, electro-optical devices, energy storage devices, energy conversion devices, information storage and processing devices, actuators, sensors, thermoelectric devices, or devices that convert electrical energy to mechanical energy through the piezoelectric effect.
[0011] A more complete understanding of the embodiments of the present disclosure may be derived by reference to the detailed description and claims when considered in conjunction with the following illustrative drawings. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 illustrates a composite material according to an embodiment of the present disclosure. [Diagram 2] FIG. 1 illustrates an element according to a further embodiment of the present disclosure. [Diagram 3] FIG. 2 illustrates another element according to an embodiment of the present disclosure. [Figure 4] 1 illustrates a semiconductor device or structure according to an embodiment of the present disclosure. [Diagram 5] FIG. 2 illustrates another element according to an embodiment of the present disclosure. [Figure 6] FIG. 1 illustrates an exemplary molecule that forms a ferroelectric nematic liquid crystal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] It is appreciated that elements in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale, for example, the dimensions of some of the elements in the figures may be exaggerated relative to other elements to help improve understanding of the embodiments illustrated in the present disclosure.
[0014] The descriptions of exemplary embodiments provided below are exemplary and intended for illustrative purposes only, and the following descriptions are not intended to limit the scope of the disclosure or claims. Moreover, the recitation of multiple embodiments having stated features is not intended to exclude other embodiments having additional features or other embodiments incorporating different combinations of the stated features.
[0015] In this disclosure, any two numbers of a variable may constitute the usable range of the variable, and any range indicated may include or exclude the endpoints. In addition, any value of an indicated variable (whether or not indicated with "about") may refer to an exact value or an approximate value, may include equivalents, may refer to an average, median, representative, majority, or value ±10% (e.g., volume %, atomic %, or mass %), etc. Furthermore, in this disclosure, the terms "comprising," "including," "comprised of," and "having" may, in some embodiments, independently refer to "typically or broadly comprising," "comprising," "consisting essentially of," or "consisting of." In this disclosure, any defined meaning does not necessarily exclude the ordinary and customary meaning.
[0016] The present disclosure generally relates to a composite material comprising a ferroelectric nematic liquid crystal. The composite material can be multifunctional, so that the composite material can be used in a variety of applications (e.g., in a capacitor, actuator, or electro-optical device). According to various embodiments, the composite material can be a dielectric material, for example, a dielectric material having a relative permittivity (relative dielectric constant) of greater than 10, or between about 2 and about 5000.
[0017] 1(a) and (b) show an element 100 including a composite material 102, according to an embodiment of the present disclosure. In the embodiment shown, the composite material 102 includes a porous material or medium 104 and a ferroelectric nematic liquid crystal 106. As shown, the porous material 104 includes a wall 108. The element 100 can also include a first electrode 110, a second electrode 112, a voltage source 114, and a switch 116.
[0018] According to embodiments of the present disclosure, the porous medium or material 104 contains ferroelectric nematic liquid crystals 106. In these cases, as illustrated in FIG. 1(a), the domain walls 108 of the porous medium 104 configure the ferroelectric nematic liquid crystals 106 to produce a morphology with randomly oriented ferroelectric domains. In this case, the composite material 102 has zero net electric polarization in the absence of an applied electric field. As illustrated in FIG. 1(b), with a sufficient electric field (e.g., about 10 3 ~about 10 6 , or about 10 7 ~about 10 9 When a high electric field (V / m) is applied to the porous medium 104, the polarization reorients and the composite 102 acquires a large net electric polarization, which exposes the walls 108 of the porous medium 104 to a large electric field that can contribute to the effective dielectric constant. Furthermore, the polar domains of the composite can be oriented by the strain field, resulting in a large piezoelectric effect without the application of an electric field, and conversely, mechanical strain can be generated by the application of an electric field. As such, these materials have potential applications in a variety of devices, including dielectric structures, high energy density capacitors, actuators and transducers, sensors, electro-optical devices, thermoelectric devices, devices that convert electrical energy to mechanical energy through the piezoelectric effect, and other devices described herein.
[0019] 1, the porous material 104 includes a plurality of pores 118 with a volume 120. The pores 118 may be defined, at least partially or completely, by walls 108. The volume 120 may be filled, or may be substantially (e.g., at least 90, 95 or 99%) filled, with ferroelectric nematic liquid crystal. The pores may be interconnected.
[0020] The porous material 104 can be a solid. By way of example, the porous material 104 can be a polymer (e.g., polyethylene, silicone, polyvinylidene fluoride, cellulose, polypeptides), a glassy material (e.g., silicate, borosilicate or aluminosilicate glass, glassy polymer), a crystalline material (e.g., silicon, silica, alumina, titanates, perovskites, LiNbO3), an amorphous material (e.g., amorphous carbon, amorphous silicon, amorphous metal), a foam (e.g., polystyrene or vinyl foam, metal oxide foam, liquid emulsion), an aerogel (e.g., formed from silica, carbon or metal oxide), or a porous ceramic (e.g., zeolite, anopore membrane, honeycomb ceramic, diatomaceous earth). The porosity of the porous material 104 can range from about 0.05 to about 0.4, or from about 0.5 to about 0.95. The pore size or average pore size of the pores in the porous material 104 can range from about 2 nm to about 50 nm, or from about 0.1 micrometers to about 10 micrometers.
[0021] The ferroelectric nematic liquid crystal 106 can include any suitable ferroelectric nematic liquid crystal material. By way of example, the ferroelectric nematic liquid crystal 106 can include ferroelectric nematic liquid crystal forming molecules, such as RM734 or DIO, as illustrated in FIG.
[0022] The electrodes 110, 112 may be formed of any suitable conductive material, such as gold, copper, aluminum, or indium tin oxide (ITO). The composite material 102 may be considered similar to a class of inorganic or polymeric materials called "relaxor ferroelectrics," which are solid-state ferroelectrics with randomly oriented nanometer-scale polar domains. This isotropic domain structure may be achieved in a variety of ways, including rapid quenching to the ferroelectric state to obtain a polycrystalline morphology with nanometer-scale ferroelectric domains, or the formation of a nanostructured composite containing randomly oriented nanometer-scale ferroelectric domains in a nanoporous host material. The term "superparaelectric" has recently been introduced to describe solid-state relaxor ferroelectrics containing nanometer-scale domains with local polar order, which are used to create dielectric capacitors with ultra-high energy density and high efficiency [YH. Chu, Science 374, pp. 33-34 (2021); H. Pan et al., Science 374, pp. 100-104 (2021)].
[0023] The main difference between the relaxor ferroelectrics described so far and the composite material described here is that the ferroelectric component used in the latter composite material is a fluid ferroelectric nematic liquid crystal rather than a solid-state inorganic or polymeric ferroelectric material. The main advantage of ferroelectric nematic materials is the ease of processing resulting from their fluidity. Ferroelectric nematic materials can be easily injected or integrated into a wide variety of porous media, including, for example, aerogels, polymer networks, inverse opals, zeolites, and nanoporous glasses and ceramics, which facilitates materials design and optimization and potentially reduces the cost of materials production.
[0024] Another major advantage comes from the discovery that structurally polar surfaces can be used to control the polarity ordering of the volume of nearby ferroelectric nematic material, such that the inherent structural polarity of the pore surface can induce a preferred polar ordering in the volume of ferroelectric material within the pore. This effect can allow each ferroelectric domain in the composite to "remember" its zero-field polar orientation, which can reduce hysteresis and associated energy losses in capacitor applications. Such surface polarity can be achieved in porous materials composed of polar polymers or inorganic materials (including solid-state ferroelectrics) with polar surface structures, or by chemical functionalization of the inner surfaces of the porous media (e.g., functionalization with one or more of silane or thiol self-assembled monolayers, oligomers, polymers, block copolymers). A further potential advantage of the composite materials described herein comes from the fast response of fluidic ferroelectric nematic materials to applied electric fields, which can allow capacitors based on these materials to be charged and discharged more quickly.
[0025] Although efficient capacitive energy storage generally requires materials with small hysteresis, composites based on ferroelectric nematic materials with large hysteresis are also of interest, as these are materials with intrinsic memory, where the state of the material is history dependent. In other words, the material properties of ferroelectric nematic composites can depend on the detailed history of the material, including the history of field treatments (e.g., due to applied electric, magnetic and optical fields, and mechanical stress and strain), as well as the variation of thermodynamic parameters (e.g., temperature, pressure and chemical potential).
[0026] Such materials with intrinsic memory represent a novel type of programmable matter with a wide range of potential applications, including as memory elements, e.g., for optical and neuromorphic computing applications, with optical, electrical or mechanical readout for information storage and processing, and as shape memory materials, e.g., for soft robotics and a variety of sensor and actuator applications and devices, with programmable shape changes driven by temperature variations, by chemical stimuli, or by optical or electric fields. Such a device may be illustrated diagrammatically as device 100.
[0027] According to further embodiments of the present disclosure, the device 100 and the composite material 102 may be used in energy conversion and energy storage devices. One approach involves creating a porous medium containing ferroelectric nematic liquid crystals in the limit that the electrical threshold for switching is large. In a system with pores of volume V and dimension a, N F The typical surface energy per unit contact area between the liquid crystal and the porous medium is W. The overall surface energy of the system is
[0028]
number
[0029] This indicates that the switching threshold, determined by the surface energy, increases as the pore size decreases. The elastic energy density due to the distortion of the liquid crystal director field is Ka -2 which also contributes to the energy threshold for electrical switching.
[0030] Here, the applicants use typical parameter values for liquid crystal properties to estimate some experimentally relevant quantities. Consider a uniformly aligned bulk ferroelectric nematic material in which the polar molecular orientation (polar director) is fixed by surface anchoring in a porous structure and subjected to an applied field E. The elastic energies of the surface and bulk are required to create a sufficiently deep energy well to prevent reorientation of the polarization field in response to a depolarizing field. A zero-order energy analysis is proposed. The electric energy density of the polarization in an applied field E is f p =-P E, and the strain energy density of the porous unit cell is f elastic =K / a 2 The maximum depolarization field arises from the polarization change E=P / ε at the electrode surface. For simplicity, let ε=ε0. Then, P=6μC / cm 2 So, f p =406J / cm 3 f elastic =f p If K=10 -11 N, a = 16 nm. In order to maintain the surface alignment in the presence of elastic torque,
[0031]
number
[0032] As shown in previous studies, the polar surface energy of a typical polymer array cell is approximately W = 3 × 10 -3 J / m 2 Therefore, the required polarization fixation can be achieved by a pore size of around 10 nm (or between about 2 nm and about 50 nm) and a polymer surface treatment (e.g., with polyimide, nylon or polypeptide), or some other treatment (e.g., silane or thiol self-assembled monolayers) that provides sufficient surface anchoring energy.
[0033] Considering a structure with a large enough energy barrier to fix the polarization direction (due to polar anchoring at the interior (pore) surfaces), referred to as a polar ordered volume, FIG. 2 shows a potential energy storage element 200 that can be charged and discharged under environmental temperature fluctuations (e.g., between day and night) and used to perform electrical work.
[0034] Similar to element 100, element 200 includes a composite material 202. Composite material 202 can be the same as or similar to composite material 102. Figure 2 illustrates the energy conversion process from heat to electricity in the polar-arranged volume of element 200 (composite material 202).
[0035] The composite material 202 fills the gap between the two conductive electrodes 204, 206 without an alignment layer. The process of converting heat to electrical energy is shown diagrammatically, starting from the top left and proceeding clockwise in the figure. F The macroscopic uniform polarization in the phase is stabilized by the polar alignment at the surface, resulting in a polarized surface charge and a resulting depolarization field. This field creates a voltage drop between the electrodes 204, 206, and when the switch 208 between the electrodes 204, 206 is closed (top center diagram), a current flows in the external circuit 210 containing the voltage source 212 to neutralize the polarization charge. This is the first discharge process. After some time, the free charges balance the polarization charge and the potential difference between the electrodes approaches zero (top right diagram). The switch 208 is then opened and the liquid crystal is heated to dissipate the N F The free charges remaining on the electrodes reduce the voltage between the electrodes 204, 206, which is the first charging process (bottom right diagram). Next, the switch 208 is closed and current flows through the external circuit 210 to neutralize the free charges (bottom center diagram). This is the second discharging process. In the final step, the switch 208 is opened and the sample is cooled to change from N phase to N phase. F Due to the polar surface anchoring, the polarization aligns in the same direction as before (top left diagram). This is the second charging process.
[0036] We can estimate the achievable energy density in the charged state (Figure 2, top left) as follows. First, calculate the total electrostatic energy F:
[0037]
number
[0038] In this formula, Q is the surface polarization charge, C is the capacitance of the liquid crystal layer with a thickness d, A is the area of the boundary surface, and V is the volume of the liquid crystal layer. At this time, the energy density (electrostatic energy density, etc.) f E is given by the following equation:
[0039]
number
[0040] Ferroelectric polarization P=6μC / cm 2 , relative permittivity ε r = 1, the energy density is 203 J / cm 3 This is an order of magnitude smaller than currently available high energy density batteries (see Table 1), however the entire charging process depicted in Figure 2 is simply achieved by heating and cooling the device. The room temperature ferroelectric nematic phase has already been demonstrated in neat materials and blends, and the transition can be driven by fluctuations in environmental temperature, for example between day and night.
[0041] [Table 1]
[0042] N F Combining liquid crystals with conventional dielectric materials has the potential to achieve much higher energy storage capacities than are currently available. The electrostatic energy stored in a parallel plate capacitor with a dielectric layer of thickness d is
[0043]
number
[0044] This energy density is calculated by dividing the thickness by N F It can be raised by partially filling it with material. In these cases, the composite material contains ferroelectric nematic regions interspersed with regions of a second dielectric material. The ferroelectric nematic regions exhibit a polarization field P(r), which in the presence of an electric field reorients parallel to the field. This reorientation causes polarization charges to build up at the interface between the ferroelectric nematic regions and the regions of the second material. When a voltage of up to Vsat=P / C, where C is the capacitance / area of the dielectric layer, is applied, N F The electric field inside the liquid crystal is screened by the reorientation of the polarization. As a result, at the applied voltage, the electric field in the composite is confined to the second material. Thus, the polarization charges apply an electric field, which can be as large as E=P / ε, to the regions of the second material. This electric field is applied to the second material without free electrons or holes coming into contact with the second material, and the ferroelectric nematic material allows charge transport by promoting the movement of bound charges that are not free charges. By this mechanism, the second material can be charged to high voltages while avoiding the dielectric breakdown caused by the cascade process of free charge carriers.
[0045] Thus, the achievable energy density of conventional thin film capacitors is limited by the breakdown electric field of the dielectric layer (best case, about 5 MV / cm, as shown in Table 2). F The advantage of the composite is that the bulk of the dielectric material is non-conductive N F The result is that the lack of charge transport can potentially increase the breakdown electric field to values much higher than known thin film dielectrics such as those shown in Table 2. F In a composite, the electric field limit is the maximum surface polarization charge: E max =P / ε0ε r ≒67MV / cm(ε r=1), which is about 10 times larger than the best thin-film capacitors. This is especially important for energy storage because N F In the composite, the energy density f E ∝E 2 , potentially implying an energy density 100 times greater.
[0046] [Table 2]
[0047] Achieving such polar ordering volumes can be technically challenging. Figure 3 shows an alternative scheme, with more easily achievable charge and discharge cycles. This process requires only non-polar ordering volumes. In other words, the ordering surface only needs to maintain a nematic-like director alignment, and there is no preference as to how the polarization orients locally. In this case, the pore dimensions can be larger, with a in the range of 1-10 mm. The ferroelectric polarization is aligned by applying a small alignment field E of 1 V / mm during cooling. The total energy required to align the material is F align = EdQ = EAdP, and when E = 1 V / mm, the energy density loss f align =EP=6×10 -5 J / cm 3 Gives.
[0048] 3, starting at the top right and proceeding clockwise, using element 300. Element 300 can be the same as or similar to element 200. In particular, element 300 can include composite material 302 (which can be the same as or similar to composite material 202), electrodes 304, 306, switch 308, and voltage source 312. Electrodes 304, 306, switch 308, and voltage source or power supply 312 can be as described above with respect to FIG.
[0049] First, switch 308 is opened to heat element 300, FThe polarized charge is then converted from N-phase to N-phase, which dissipates the polarization charge at the boundary surface. When switch 308 is closed, the remaining free charges create a voltage drop that drives a current in an external circuit 310 (bottom center diagram). After all free charges have been neutralized, the sample is cooled in the presence of a small aligning field provided by an external power supply, e.g., voltage source 312, to convert the polarized charge from N-phase to N-phase. F The power supply 312 can continuously supply current to the electrodes 304, 306 to balance the polarization charges. As a result, the electric field in the sample is always E. The absence of a large depolarizing field relaxes the requirement for strong volume alignment.
[0050] 4 illustrates a semiconductor device or structure 400 according to yet an additional embodiment of the present disclosure. In the illustrated embodiment, the semiconductor device 400 includes a substrate 402, a composite material 404, and an additional layer 406.
[0051] The substrate 402 can include or be formed on any underlying material or material that can be used to form a device, circuit, or film. The substrate can include a bulk material, such as silicon (e.g., single crystal silicon), other Group IV materials, such as germanium, or other semiconductor materials, such as Group II-VI or Group III-V semiconductor materials, and can include one or more layers overlying or underlying the bulk material. Additionally, the substrate can include various features, such as depressions and protrusions, formed within or on at least some of the layers of the substrate. By way of example, the substrate can include a semiconductor material. The semiconductor material can include or be used to form one or more of the source, drain, or channel regions of the device. The substrate can further include an interlayer dielectric (e.g., silicon oxide) and / or a high-k material layer overlying the semiconductor material. In this context, a high-k material or high-k dielectric material is a material that has a dielectric constant higher than that of silicon dioxide.
[0052] Composite material 404 may be or include any composite material or dielectric medium described herein, such as composite material 102. The additional layer 406 may include any suitable layer. By way of example, the additional layer 406 may be or include a conductive layer, such as a metal layer.
[0053] According to additional embodiments of the present disclosure, the composite material, or more particularly the dielectric medium, includes a ferroelectric nematic liquid crystal and a solid material, the solid material being present (e.g., dispersed) in the liquid crystal as particulates. The solid material may be comprised of ferroelectric or superparaelectric particles, such as LiNbO3, BaTiO3, or lead zirconate titanate (PZT).
[0054] According to embodiments of the present disclosure, the dispersion is formed by phase separation or photopolymerization. The dispersion can be stabilized by amphiphilic molecular components, such as anionic or cationic lipids, non-ionic surfactants, or ionic liquids.
[0055] 5 shows an element 500 that includes a composite / dielectric material 502 that includes a solid material dispersed in a liquid crystal, and electrodes 504 and 506. Electrodes 504 and 506 can be the same as or similar to electrodes 110, 112.
[0056] The device 500 can be used for energy storage and / or energy conversion schemes utilizing a variety of energy sources. For example, a ferroelectric nematic material doped with photoresponsive dye molecules converts N FThe ferroelectric nematic material can be driven from the N-phase to the N-phase (or isotropic phase) (photoinduced phase transition) and can convert electromagnetic energy (e.g. sunlight) into electrical energy. A very similar "charge pump" approach utilizing ferroelectric smectic liquid crystals has been proposed previously [M. Knezevic and M. Warner, "Photoferroelectric solar to electrical conversion", Applied Physics Letters 102, 043902 (2013)]. The present invention differs from this prior art in that it utilizes a composite material containing ferroelectric nematic material in a porous medium or dispersion to achieve high efficiency energy conversion, and in that it uses the recently discovered phenomenon of polar anchoring to achieve volume polar ordering of the ferroelectric nematic material.
[0057] The exemplary embodiments of the disclosure above are not intended to limit the scope of the present invention, as these are merely examples of embodiments of the present invention, as defined by the appended claims and legal equivalents. For example, examples of the present disclosure may include composite materials including multiple layers, at least partially filled with ferroelectric nematic liquid crystal or dielectric medium described herein, with voids or one or more pores between the layers. Any equivalent embodiments are intended to be within the scope of the present invention. Various embodiments of the present disclosure, in addition to those shown and described herein, such as alternative useful combinations of the described elements, may become apparent to those skilled in the art from the description. Such modifications and embodiments are also intended to be included within the scope of the appended claims.
Claims
1. 1. A composite material comprising: a first porous material having pores, the pores having a volume; and a ferroelectric nematic liquid crystal, A composite material, wherein the pore volume of said first porous material contains ferroelectric nematic liquid crystal.
2. 10. The composite material of claim 1, wherein the pore volume of the first porous material is substantially filled with ferroelectric nematic liquid crystal.
3. The composite material of claim 1 , wherein the first porous material is a solid.
4. The composite material of claim 1 , wherein the first porous material is a polymer.
5. The composite material of claim 1 , wherein the first porous material is vitreous.
6. The composite material of claim 1 , wherein the first porous material is crystalline.
7. The composite material of claim 1 , wherein the first porous material is amorphous.
8. The composite material of claim 1 , wherein the first porous material is a foam.
9. The composite material of claim 1 , wherein the first porous material is an aerogel.
10. The composite material of claim 1 , wherein the first porous material is a porous ceramic.
11. An electro-optical element comprising the composite material of claim 1 .
12. 1. A semiconductor structure comprising: a porous solid material having pores, the volume of the pores of the porous solid material comprising a ferroelectric nematic liquid crystal.
13. A dielectric structure comprising a porous, solid, electrically insulating material having pores, the volume of the pores of the porous, solid, electrically insulating material containing a ferroelectric nematic liquid crystal.
14. 1. A capacitor comprising a dielectric medium comprising a porous, solid, electrically insulating material having electrodes and pores, the volume of the pores of the porous, solid, electrically insulating material containing a ferroelectric nematic liquid crystal.
15. A dielectric medium comprising a ferroelectric nematic liquid crystal and a solid material, the solid material being dispersed as fine particles in the liquid crystal.
16. A dielectric medium comprising ferroelectric nematic liquid crystal and a solid material, said solid material being composed of ferroelectric or superparaelectric particles.
17. A dielectric medium comprising a dispersion of ferroelectric nematic liquid crystal and a solid material, said dispersion being formed by phase separation.
18. A dielectric medium comprising a dispersion of ferroelectric nematic liquid crystal and a solid material, said dispersion being formed by photopolymerization.
19. A dielectric medium comprising a dispersion of ferroelectric nematic liquid crystal and a solid material, said dispersion being stabilized by an amphiphilic molecular component.
20. 20. A device comprising a composite material or a dielectric medium according to any one of claims 1 to 7, 10 to 13 and 15 to 19.
21. 21. The device of claim 20 which is an energy storage device.
22. 21. The element of claim 20 which is an energy conversion element.
23. 21. The device of claim 20 which is an information storage and processing device.
24. 21. The element of claim 20 which is an actuator, a sensor, a thermoelectric element, or an element that converts electrical energy into mechanical energy through the piezoelectric effect.
25. 14. The composite material of any one of claims 1 to 7 and 11 to 13, which is a dielectric material.